1972
DOI: 10.1007/bf00187705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mirex on the larval development of two crabs

Abstract: Abstraet. The effects of mirex, a chlorinated hydrocarbon used to kill the imported red ant, Solenopsis saevissima richteri, on the complete larval development of two crabs, Rhithropanopeus harrisii and Menippe mercenaria are described. The duration of developmental stages of Rhithropanopeus and the total time of development is generally lengthened with an increase in concentration of mirex from 0.01 to 10.0 ppb. There are highly significant differences between survival of larvae in the control and in each con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 6 publications
(2 reference statements)
2
8
0
Order By: Relevance
“…Buchanan et al (1970) observed delay in the moulting of larvae reared in sublethal concentrations of sevin from zoeal stages I to 11. Similar results have been reported for the zoeal stages of R. harrisii, Menippe mercenaria and C. sapidus by Bookhout et al (1972Bookhout et al ( , 1976 caused by different pollutants.…”
Section: Mean Days Of Moultingsupporting
confidence: 78%
“…Buchanan et al (1970) observed delay in the moulting of larvae reared in sublethal concentrations of sevin from zoeal stages I to 11. Similar results have been reported for the zoeal stages of R. harrisii, Menippe mercenaria and C. sapidus by Bookhout et al (1972Bookhout et al ( , 1976 caused by different pollutants.…”
Section: Mean Days Of Moultingsupporting
confidence: 78%
“…For Penaeus monodon, sensitivity to nitrate may be related to ontogeny and natural habitat. Thus, Crustacea are reported to be more susceptible to toxins during ecdysis (Duke et al 1970, Nimmo et al 1971, Bookhout et al 1972, Armstrong et al 1976, and in the present study the protozoea moulted from Protozoea I to Protozoea II stage during the experimental period. With respect to habitat, P. monodon larvae occur naturally in offshore, tropical regions (Motoh 1985) which typically contain extremely low levels of dissolved nitrate (Spencer 1975).…”
Section: Discussionmentioning
confidence: 88%
“…Similar results have been reported also elsewhere. Bookhout et al (1972) and Bookhout & Costlow (1975) studied the effect of mirex, a chlorinated hydrocarbon on the larval development of the crabs Rhithropanopeus harrisii (Gould, 1841), Menippe mercenaria (Say, 1818) and Callinectes sapidus (Rathbun, 1896) and found that as the test concentration increased the number of larvae reaching the megalopa stage decreased. While studying the effects of methyloxychlor on larval development of R. harrisii and C. sapidus, they also noted that the sharpest reduction in survival took place in the megalopa stage.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, stress at higher concentrations of pollutants may exert an action on the mechanism which regulates morphological and moulting changes and hence faster development of larvae (Bookhout et al 1972). Moulting in crab larvae is known to be a neuroendocrine function (Costlow 1963(Costlow , 1966 and naturally sublethal toxicity of neurotoxins may also interfere with moulting.…”
Section: Discussionmentioning
confidence: 99%